VOICE ON QUANTITATIVE METHODS IN RISK MANAGEMENT BY AN AIR OPERATOR - Piotr MAKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2020)
This article is devoted to the diagnosis of problems arising from risk management obligations under the safety management system implemented in civil organisations of certified air operators (carriers). Focus was on the use of quantitative methods in safety risk analysis. The idea of an approach to determine the probability of accidents and serious incidents based on the intensity of symptoms with lower consequences and risk factors as a function of time or number of performed air operations was proposed, based on Markov discrete processes [6,10-12,16]. The essence of this approach is explained by the mathematical model of Runway Excursion probability during landing operations. The concept of improvement of operators' cooperation in the exchange of information about safety indicators by profiling the organisation was presented. The last proposal concerns the construction of a comprehensive risk assessment indicator using a safety risk matrix.